2017
DOI: 10.1002/jcc.25136
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relevance of thiophene rings as bridge unit in acceptor‐bridge‐donor dyes on self‐aggregation and performance in DSSCs

Abstract: The possibility of dye charge recombination in DSSCs remains a challenge for the field. This consists of: (a) back-transfer from the TiO to the oxidized dye and (b) intermolecular electron transfer between dyes. The latter is attributed to dye aggregation due to dimeric conformations. This leads to poor electron injection which decreases the photocurrent conversion efficiency. Most organic sensitizers are characterized by an Acceptor-Bridge-Donor (A-Bridge-D) arrangement that is commonly employed to provide ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Based on the physical data above, when considering the utility of these dyes for DSSC applications, the HOMO orbital resides at a favourable energy when considering the common electrolytes and regeneration dynamics. 31 In addition, each of these dyes possess LUMO orbitals situated on the acceptor units, and therefore injection should be kinetically favourable. When compared to benchmark L1, the blue shifted or weaker absorbing profiles of OA1, OA2 and OA3 may manifest in weaker device performance, but the addition of multiple redox active centres may increase the redox robustness of the dye, and could improve electron injection rates.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the physical data above, when considering the utility of these dyes for DSSC applications, the HOMO orbital resides at a favourable energy when considering the common electrolytes and regeneration dynamics. 31 In addition, each of these dyes possess LUMO orbitals situated on the acceptor units, and therefore injection should be kinetically favourable. When compared to benchmark L1, the blue shifted or weaker absorbing profiles of OA1, OA2 and OA3 may manifest in weaker device performance, but the addition of multiple redox active centres may increase the redox robustness of the dye, and could improve electron injection rates.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study by Zarate et al 191 also studied dye-sensitized solar cell models, employing both B3LYP with added dispersion corrections and CAM-B3LYP. Here, CAM-B3LYP was employed to calculate the vertical excitation energy, and a comparison to values as calculated by the ωB97X-D, BHHLYP, M06-2 Â, M11, HISSbPBE, HSE06, M06, PBE, and TPSSh functionals was performed.…”
Section: Dye-sensitized Solar Cell Applicationsmentioning
confidence: 99%
“…[32][33][34] Additionally, dyes with these spacers are expected to show efficient CT, which can be used in both linear and non-linear optics, with prospective uses in optical computing, optical signal processing, telecommunications, and additional applications as a bridge for DSSCs. 15,35 In this context, with a D-A system and thiophene as a p-conjugated bridge, Kim et al produced dyes based on phenothiazine (PTZ) and cyanoacrylic acid, which indicated that the thiophene bridge affects DSSC performance. 36 A few theoretical and experimental investigations have been published on azo dyes with low PCE DSSC applications.…”
Section: Introductionmentioning
confidence: 99%